2020
DOI: 10.5223/pghn.2020.23.5.472
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Effects of Severe Late-Onset Hyponatremia on Long-Term Growth of Prematurely Born Infants

Abstract: Purpose: Sodium is an essential nutritional electrolyte that affects growth. A low serum sodium concentration in healthy premature infants beyond 2 weeks of life is called lateonset hyponatremia (LOH). Here, we investigated the association between LOH severity and growth outcomes in premature infants. Methods: Medical records of premature infants born at ≤32 weeks of gestation were reviewed. LOH was defined as a serum sodium level <135 mEq/L regardless of sodium replacement after 14 days of life. Cases were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 19 publications
0
27
1
1
Order By: Relevance
“…Another study found sodium to stimulate cell proliferation and also play a role in protein turnover; thus, it can be considered a significant growth factor [22]. In contrast to our findings, a recent study reported that LOH does not affect the future growth of premature neonates [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Another study found sodium to stimulate cell proliferation and also play a role in protein turnover; thus, it can be considered a significant growth factor [22]. In contrast to our findings, a recent study reported that LOH does not affect the future growth of premature neonates [23].…”
Section: Discussioncontrasting
confidence: 99%
“…Таким образом, признано, что детям с БЛД необходимо на 15-20% больше энергии, чем недоношенным без БЛД -в диапазоне 120-150 ккал/кг/сут; но при активном течении (обострении) БЛД -не менее 140 ккал/кг/сут, причем в относительно небольшом объеме получаемого питания, что представляет сложную задачу для врача [84,85]. Следует учитывать, что длительное применение некоторых медикаментов (стероидов и петлевых диуретиков) при ограниченном потреблении жидкости -это дополнительный фактор риска развития остеопении у детей с БЛД [86,87].…”
Section: Clinical Phenotypes Of Malnutrition In Young Children: Diffe...unclassified
“…When hypernatremia (defined as serum sodium >150 umol/l) occurs, the causes is often inadequate free water administration, and may be associated with clinical evidence of volume depletion. Optimizing the fluid intake and free water will be the first step in management ( 98 – 101 ). When hypernatremia occurs without volume depletion in AKI, minimizing additional delivered sodium from red blood cell transfusion, albumin infusions, parenteral nutrition, carrier solutions for other medications, is especially important in first few days of life as increased IVH are seen in the context of early hypernatremia ( 102 ).…”
Section: Assessment and Managementmentioning
confidence: 99%